The Elephanta suite - Theroux, Paul. (Boston : Houghton Mifflin, 2007)
Contains three connected novellas about Westerners whose lives are changed through their trips to India.
Monkey Hill -- The gateway of India -- The elephant god.
Booklist.
Kirkus Starred.
Library Journal.
Adult
Keywords: Americans -- India -- Fiction; Americans -- India -- Fiction; India -- Fiction; India -- Fiction